Influence of the electrostatic plasma lens on the emittance of a high current heavy ion beam - Chekh, Yu.; Goncharov, A.; Protsenko, I. (Вопросы атомной науки и техники, 2005)
We describe results of experimental emittance investigations of a high-current heavy metal ion beam focused by an electrostatic plasma lens. A pulsed beam of Cu ions with energy 16 keV, duration 100 µs, and total current up to 500mA was produced by a MEVVA type ion source. A “pepper-pot” technique was used to measure the emittance of the beam. We find that, under conditions appropriate for optimal beam focusing, the emittance corresponding to a current of 250 mA is 1.6 π⋅mm⋅mrad and is conserved in beam transport through the lens.